ANALYSIS AND DISTANCE ACCESS DESIGN FAR WITH VPN TECHNOLOGY IN BMT OFFICE. MENTARI EAST LAMPUNG - Arif Hidayat (STMIK Pringsewu Lampung, 2019)
Along with the widespread use of the internet, many companies then switch to using the internet as part of their network to save costs. However, security issues are still a major factor in the reliability of a network. Virtual Private Network (VPN) is one way that can be used to create a private network and long-distance connections (remote access) with a high level of security over public networks or the Internet. The conclusions of this study are a) analysis and design of remote access with VPN technology in the Mentari East Lampung BMT Office, b) the resulting management of IP Address distribution for connections between branches using VPN, c) the creation of a VPN account management function for connection between branch BMT office. Mentari East Lampung, d) has successfully tested the VPN account login from the Client side.